Systematically Studying the Optimal Amino Acid Distribution Patterns of the Amphiphilic Structure by Using the Ultrashort Amphiphiles - He, Shiqi; Yang, Zhanyi; Yu, Weikang; Li, Jiawei; Li, Zhongyu; Wang, Jiajun; Shan, Anshan (Frontiers in Microbiology, 2020)
Amphipathicity has traditionally been considered to be essential for the de novo design or systematic optimization of antimicrobial peptides (AMPs). However, the current research methods to study the relationship between amphiphilicity and antimicrobial activity are inappropriate, because the key parameters (hydrophobicity, positive charge, etc.) and secondary structure of AMPs are changed. To systematically and accurately study the effects of amphiphilicity on antimicrobial properties of AMPs, we designed parallel series of AMPs with a different order of amino acids in a sequence composed only of Arg and either Trp (WR series) or Leu (LR series), under conditions in which other vital parameters were fixed. Furthermore, based on the WR and LR peptides that can form stable amphiphilic β-sheet structures in the anionic membrane-mimetic environment, we found that high β-sheet amphipathic was accompanied by strong antimicrobial activity. Of such peptides, W5 ([RW]4W) and L5 ([RL]4L) with a nicely amphipathic β-sheet structure possessed the optimal therapeutic index. W5 and L5 also exhibited high stability in vitro and a potent membrane-disruptive mechanism. These results suggest that the alternate arrangement of hydrophobic and hydrophilic residues to form a stable amphipathic β-sheet structure is an essential factor that significantly affects the antimicrobial properties.